Knowledge management at Tata Chemicals, Mithapur - Verma, Sanjay, (SAGE Knowledge. Cases., 2016)
Dr. Devsen (Dev) reflected on the initiatives in Knowledge Management (KM) at the Mithapur Unit of Tata Chemicals Limited (TCL), a company that produced a diversified range of chemicals from soda ash to salt. The initiatives were designed to foster innovation by encouraging the systematic harvesting and sharing of knowledge which enabled the employees to share their experiences and reflections on what happened in the unit.